Status of Heavy Metals and Remediation Potential of Indigenous Plants at Contaminated Benin City and Abudu Sites of Edo, Nigeria - Osarobo Okonokhua , Boris; Robert Orhue, Ehi (International Journal of Environment, 2024)
Assessment of heavy metals (HMs) concentrations and remediation potential of indigenous plants in urban environments are necessary for safeguarding and restoring soil quality. This study evaluated the status of total HMs and remediation potential of the predominant plant species growing at contaminated sites in both Benin City and Abudu. The species were sampled along with soil around auto-mechanic workshops and from two respective uncontaminated sites and analyzed for total concentrations of eight metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn) with an Atomic Absorption Spectroscopy. The geo-accumulation index revealed that both sites were extremely polluted with four HMs in the order of Fe > Zn > Mn > Cu. Benin was severely polluted with Pb, Cd and Cr and moderately to highly polluted with Ni, while Abudu was moderately to severely polluted with Pb and Cd, moderately polluted with Cr and slightly polluted with Ni. Eleucine indica identified at Abudu and Perperomia pellucida in Benin City were both found to contain toxic levels of four HMs (Fe, Zn, Cd and Cr), only E. indica at Abudu was found to exceed the limit of Cu, Pb and Ni set for plants while the level of Mn in both species were far from the permissible limit set by WHO. No plant was proven to be a hyperaccumulator but such potential towards Zn, Pb and Cd was observed for E. indica while the same phenomenon could be ascribed to P. pellucida for Cu and Zn if assisted with soil amendment. Heavy metal pollution levels of the sites demand clean up and predominant indigenous plant species can be used to manage them.